Watching self from a distance: The whys of watching sinetrons among Malay-Javanese women in Malaysia - Rofil, Lily El ferawati (Universitas Negeri Yogyakarta, 2017)
This article discusses the cognitive reasoning behind the love for watching sinetron expressed by Malay-Javanese women in Malaysia. The Malay-Javanese women in this context refer to female members of Javanese communities within Malay society. Malaysians of Javanese descent are constitutionally considered as ethnic component of Malay racial group due to similarities in cultural customs and religion of Islam. However, they retain some semblance of Javanese cultural heritage including speaking the language in their everyday life. In the context of Malay-Javanese women under this study, it is identified that sinetrons have become the main source of their cultural consumption from television. Sinetrons are soap opera-like television productions from Indonesia